2004
DOI: 10.1373/clinchem.2004.038869
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pyrimidine Synthesis “de Novo” Intermediates in Urine and Dried Urine Filter- Paper Strips with HPLC–Electrospray Tandem Mass Spectrometry

Abstract: Background:The concentrations of the pyrimidine "de novo" metabolites and their degradation products in urine are useful indicators for the diagnosis of an inborn error of the pyrimidine de novo pathway or a urea-cycle defect. Until now, no procedure was available that allowed the analysis of all of these metabolites in a single analytical run. We describe a rapid, specific method to measure these metabolites by HPLC-tandem mass spectrometry. Methods: Urine or urine-soaked filter-paper strips were used to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 21 publications
(22 reference statements)
4
16
0
Order By: Relevance
“…Ureidosuccinic acid (or carbamoylaspartic acid) is an intermediary product in both aspartate and pyrimidine synthesis. Ureidosuccinic acid can be detected in urine (van Kuilenburg et al, 2004) and was previously reported to associated with prostate cancer progression (Sreekumar et al, 2009). Our data also found concentration alteration of two tetrapeptides (GlyCysAlaLys and AspAspGlyTrp) in urine of BCa patients.…”
Section: Discussionsupporting
confidence: 79%
“…Ureidosuccinic acid (or carbamoylaspartic acid) is an intermediary product in both aspartate and pyrimidine synthesis. Ureidosuccinic acid can be detected in urine (van Kuilenburg et al, 2004) and was previously reported to associated with prostate cancer progression (Sreekumar et al, 2009). Our data also found concentration alteration of two tetrapeptides (GlyCysAlaLys and AspAspGlyTrp) in urine of BCa patients.…”
Section: Discussionsupporting
confidence: 79%
“…Concentrations of the pyrimidine nucleoside metabolites and their degradation products that eluted from the Partisil-SAX HPLC column within 4 min were determined using HPLC tandem mass spectrometry, essentially as described before (14). period, the cell extracts were prepared and subjected to HPLC analysis as described above.…”
Section: Identification Of Nucleosides and Nucleobases In Cem Cell Cumentioning
confidence: 99%
“…CEM cell extracts were then exposed to the 3F-3DUrd 5Ј-monophosphate, and [ 14 14 C]OA (ϳ5-fold more UMP than OMP was formed at each time point). In the presence of K-oxonate, OMP was detected only in trace amounts, and UMP was virtually undetected (Fig.…”
Section: F-3durd Inhibits the Odc Activity Of Umps (Oprt/odc) Inmentioning
confidence: 99%
“…A 3-5 mm punch is taken from the sample spot, the analytes are removed by liquid extraction, and the extracts are analyzed by conventional bioanalytical techniques. The benefits of the approach for sampling plasma and urine have been discussed in detail [3][4][5][6][7][8]. Study costs in toxicological species can be significantly reduced because the small volumes sampled eliminates the need for satellite TK groups.…”
Section: Introductionmentioning
confidence: 99%